Learning Ember.js - Gonzales, Jason (Infinite Skills, 2015)
"In this Learning Ember.js training course, expert author Jason Gonzalez will teach you how to create a single-page app using Ember.js. Throughout the course, you will be working on building a grocery shopping list app. This course is designed for users who have experience with HTML, CSS, and JavaScript, although no experience with Ember.js is required. You will start by learning about the concepts for making the app, including setting up the wireframe, then jump into learning the basic styles for creating and displaying categories. From there, Jason will teach you how to build the model for categories and create category pages. This video tutorial will also cover creating and displaying items, and how to work with categories. Finally, you will learn how to delete and edit items and categories."--Resource description page.